Comparative Pharmacovigilance Analysis of Approved and Repurposed Antivirals for COVID-19: Insights from EudraVigilance Data - Paul Andrei Negru; Delia Mirela Tit; Andrei Flavius Radu; Gabriela Bungau; Raluca Anca Corb Aron; Ruxandra Cristina Marin (Biomedicines)
Background/Objectives: During the COVID-19 pandemic, several antivirals were approved or repurposed, but their safety profiles have not been fully compared. Pharmacovigilance data help clarify how these drugs perform in real-world use. Methods: This study performed a comparative pharmacovigilance analysis of eight antivirals used or tested during the COVID-19 pandemic, based on individual case safety reports (ICSRs) retrieved from the EudraVigilance database, reported up to 9 February 2025 and extracted from the official platform on 12 February 2025. Adverse reactions were assessed by system organ class (SOC), demographic patterns, and seriousness, and disproportionality analysis (reporting odds ratio (ROR)) was conducted to identify potential safety signals. Results: A total of 64,776 ICSRs were analyzed. Among approved antivirals, nirmatrelvir/ritonavir (NTV/r) accounted for 13.4% (n = 8693) of reports, while remdesivir (RDV) represented 6.3% (n = 4105). Repurposed antivirals such as ribavirin and lopinavir/ritonavir dominated the dataset, together making up over 80% (n = 51,978) of all reports. RDV was associated with a high proportion of serious adverse events (84%, n = 3448), and showed consistent ROR signals in hepatobiliary, renal, cardiac, and general disorders, with values exceeding 2 in several comparisons. NTV/r displayed a milder overall profile, but with positive RORs for psychiatric disorders, gastrointestinal disorders, and product-related issues. The most affected SOCs across all drugs included general disorders (31.6%, n = 20,493), gastrointestinal (19.5%, n = 12,625), nervous system (17.8%, n = 11,511), and investigations (20.4%, n = 13,219). Demographic analysis showed that most events occurred in adults aged 18–64, with RDV more often reported in elderly patients and NTV/r more frequently associated with reports from female patients and non-healthcare reporters. Conclusions: This study highlights distinct pharmacovigilance profiles of COVID-19 antivirals and supports the role of real-world data in guiding safer therapeutic choices.